THE INFLUENCE OF BICYCLING FACILITIES QUALITY ON MOTIVATION OF CYCLING TO WORK IN JAKARTA - Sarfina, Ulayya
As one of the big cities in Indonesia, the development of DKI Jakarta as a sustainable city must be supported by environmentally friendly transportation. While people's mobility still depends on motorized vehicles, cycling boom phenomenon happens due to the COVID-19 pandemic. As a group with a relatively high intensity of movement, workers in DKI Jakarta are the most affected by policies related to mobility during a pandemic, especially in terms of commuting to work. However, this crisis can be a momentum for implementing environmentally friendly transportation with non-motorized transportation (NMT). Therefore, this study aims to analyze the main factors that are considered by workers in DKI Jakarta in using bicycles to work based on the perceptions of workers in the Sudirman-Thamrin area. The approach used in this research is Confirmatory Factor Analysis (CFA) using Structural Equation Modeling (SEM). The result is physical conditions (KF), conditions of bicycle paths (JS), conditions of bicycling facilities (FS), public transportation services (TP), obstacles in cycling (HS), and subjective norms (NS) are factors that significantly affect workers’ interest in using bicycle to work. The subjective norm latent variable is the most dominant variable on the formation of interest in using bicycles to work. In addition, all the indicators forming the latent variables in this study also have a significant impact on the latent variables. The most dominant indicators for each latent variable are being able and able to use bicycles (KF), availability of special signs and markings (JS), accessibility to bike sharing spot (FS), integration of public transportation services with bicycle facilities (TP), occupancy of bicycle lanes by illegal parking and street vendors (HS), and comfort during cycling in all weather/climate (NS).